2000
DOI: 10.3354/meps205195
|View full text |Cite
|
Sign up to set email alerts
|

Induction and elimination of bulky benzo[a]pyrene-related DNA adducts and 8-oxodGuo in mussels Mytilus galloprovincialis exposed in vivo to B[a]P-contaminated feed

Abstract: With the aim of developing biomarkers of polycyclic aromatic hydrocarbon (PAH) genotoxicity for biomonitoring of the marine environment, the formation of DNA adducts and oxidative DNA damage was studied in the sentinel organism Mytilus. Mussels M. galloprovincialis were exposed for 21 d to different doses of benzo[a]pyrene (B[a]P) (50 and 100 mg B[a]P kg -1 dry wt mussel d -1 ) via trophic intake. The kinetics of B[a]P concentration in whole mussel tissues was determined in both groups, and a dose-response stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 66 publications
4
26
0
Order By: Relevance
“…Field experiments confirmed this finding since the high level of 8-oxodG in marine mussels from urban/industrialized sites contaminated PAHs was decreased after a 1 month depuration experiment in clean water (Emmanouil et al 2008). We have previously detected 8-oxodG in gills of freshwater mussel exposed to BaP (Michel and Vincent-Hubert 2012) as observed for marine mussel (Akcha et al 2000). Other model contaminants commonly found in freshwater and sea water such as Cr(VI) and Cd can also induced oxidative DNA lesions in bivalves.…”
Section: Introductionsupporting
confidence: 82%
“…Field experiments confirmed this finding since the high level of 8-oxodG in marine mussels from urban/industrialized sites contaminated PAHs was decreased after a 1 month depuration experiment in clean water (Emmanouil et al 2008). We have previously detected 8-oxodG in gills of freshwater mussel exposed to BaP (Michel and Vincent-Hubert 2012) as observed for marine mussel (Akcha et al 2000). Other model contaminants commonly found in freshwater and sea water such as Cr(VI) and Cd can also induced oxidative DNA lesions in bivalves.…”
Section: Introductionsupporting
confidence: 82%
“…However, the usefulness of this assay is debated (Kriek et al, 1998;Mitchelmore and Chipman, 1998;Akcha et al, 2000;Shugart, 2000;Ching et al, 2001;Palmqvist et al, 2003) and in relation to the findings of this study the recommendation of DNA damage as a relevant biomarker of exposure is dubious. In the present study, there was indication of a poorer survival in the sensitive Capitella sp.…”
Section: Discussionmentioning
confidence: 94%
“…I. Both metabolites could potentially be further biotransformed into the mutagenic 2,3-diol Flu and 7,8-diol Flu, which may form adducts to the nucleoside in the DNA molecule and may result in DNA helix distortion or in labile AP-sites (Carr and Hoekstra, 1995;Akcha et al, 2000;Palmqvist et al, 2003). Even though Capitella sp.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of mussels' cells to recover from oxidative DNA damage was also demonstrated in the digestive gland of Mytilus galloprovincialis. Upon in vivo exposure to benzo[a]pyrene (B[a]P), a decrease in 0 -deoxyguanosine) value to the control level was recorded after 5 days of depuration, while bulky adducts still persisted at the end of the 10-day recovery period [Akcha et al, 2000]. Similar results were found by de Almeida et al [2005] who observed reduction in 8-oxodGuo levels in gills of the mussel Perna perna (induced by exposure to air) to the control level after only 3 hr of resubmersion.…”
Section: Discussionmentioning
confidence: 99%